The Factor of Listening in Karl Jaspers’ Philosophy of Communication - Górniak-Kocikowska, Krystyna (Philosophical Faith and the Future of Humanity, 2012)
Jaspers’ views on communication and his approach to the question of listening, both underwent an evolution in which World War II and the first years thereafter played a crucial role. In this process, Jaspers journeyed from listening to the great minds of the past, through an inward dialogue with them, to one-sided lecturing while his audience was engaged in a straight-line listening, to an intimate dialogue with those he considered like-minded, to a multi-faceted dialogue, and finally to listening to his contemporaries and learning how to practice transactional listening-in-conversation in the process of a multi-layered communication he called a loving struggle. This evolution, paralleled by the transition of Japers’ philosophy from local-centered to world-centered makes his thinking attractive and useful today.
Citation Key Alias: lens.org/035-525-517-724-768
Keywords: German Student; Great Mind; Nazi Regime; Political Involvement; Verbal Communication; dept.phi